CPC-090 Mupirocin Resistant Meticillin-Resistant Staphylococcus Aureus (MRSA) – Do Patients Get the Correct Decolonisation After Screening?. (12th March 2013) - Howard, P; Morris, K
Abstract : Background: MRSA screening has been mandatory in England for two years. Mupirocin is used routinely for MRSA-positive patients but there is some resistance. Purpose: A prospective audit was undertaken of all mupirocin-resistant MRSA screens to see if patients were put on the correct treatment. Materials and Methods: From October 2011, all in-patients with high level mupirocin or neomycin MRSA resistance were followed up by a pharmacist. Patients on ineffective decolonisation regimes were changed to the correct regime, and ward staff educated. Results to March 2012 were shared, and then monthly thereafter. Education was delivered at speciality and ward level. Any subsequent failures were reported as clinical incidents. Results: The percentage of patients that were MRSA positive on screening on admission into hospital or at pre-elective screening remained stable at 2.3% during both periods. Worryingly high-level mupirocin resistance had increased from 12.2% to 19.7%. It had doubled to 24% by June! Despite audit, education and feedback, the proportion of patients with known MRSA on admission and those still in hospital when the result from the admission screen was released, on the correct decolonisation regime, got worse. There has been no improvement using senior staff or ward infection control link nurses to rebrief their staff on the documented procedure. Conclusions: MRSA carriage on screening is low. Current systems appear too complex despite multiple interventions. As a failsafe, these patients should be followed up. Posters and screensavers have since been introduced. The prospective audit continues. All centres should review their current practise to ensure patients get prescribed effective MRSA decolonisation. No conflict of interest.